2017
DOI: 10.1091/mbc.e17-06-0408
|View full text |Cite
|
Sign up to set email alerts
|

Differential context-specific impact of individual core promoter elements on transcriptional dynamics

Abstract: The roles of individual core promoter elements in transcriptional dynamics of MHC class I gene expression were determined by smFISH in primary B-cells. The elements individually modulated transcriptional bursting, differentially contributing to burst size or burst frequency, to enable combinatorial fine-tuning of the level of transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Typically, the in vivo molecular mechanism of transcription factor action is inferred from measurements of transcriptional noise obtained through snapshots of dead and fixed embryos or cells using theoretical models (Zenklusen et al, 2008; So et al, 2011; Little et al, 2013; Jones et al, 2014; Senecal et al, 2014; Xu et al, 2015; Padovan-Merhar et al, 2015; Skinner et al, 2016; Bart-man et al, 2016; Zoller et al, 2018; Hendy et al, 2017). In contrast, MS2-based live imaging can directly inform on the dynamics of transcriptional bursting in real time.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the in vivo molecular mechanism of transcription factor action is inferred from measurements of transcriptional noise obtained through snapshots of dead and fixed embryos or cells using theoretical models (Zenklusen et al, 2008; So et al, 2011; Little et al, 2013; Jones et al, 2014; Senecal et al, 2014; Xu et al, 2015; Padovan-Merhar et al, 2015; Skinner et al, 2016; Bart-man et al, 2016; Zoller et al, 2018; Hendy et al, 2017). In contrast, MS2-based live imaging can directly inform on the dynamics of transcriptional bursting in real time.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, variation in r could indicate that transcription factors play an active role in the recruitment of RNAP to the promoter or in the release of RNAP from promoter-proximal pausing (38). Typically, the in vivo molecular mechanism of transcription factor action is inferred from measurements of transcriptional noise obtained through snapshots of dead and fixed embryos or cells using theoretical models (26,(31)(32)(33)(39)(40)(41)(42)(43)(44)(45)(46)(47). In contrast, MS2-based live imaging can directly inform on the dynamics of transcriptional bursting in real time.…”
Section: Mean Transcription Rate Is Dictated By Bursting Through Modumentioning
confidence: 99%
“…Recent studies have shown that enhancers control burst fraction in Drosophila embryos (16) and mammalian erythrocytes (17). Individual core promoter elements of a major histocompatibility complex class I gene promoter contribute to burst frequency, size, or both in response to ␥-interferon stimulation (18). The transcription factor concentration, after MAPK induction, also modulates the c-Fos burst fraction in cultured cells (19).…”
mentioning
confidence: 99%